Polyetherimide energy storage composite dielectric film with multi-layer structure and application of polyetherimide energy storage composite dielectric film

By introducing 4-N,N-dimethylaminophenylboric acid and tetrafluorotetracyanoquinolinedimethylantimethyl in polyetherimide energy storage composite medium, a bifunctional symmetric three-layer structure was constructed, and the high temperature conditions were solved The problems of large dielectric loss and poor energy storage performance have achieved efficient improvement in energy storage performance and maintenance of long-term durability characteristics.

CN119410010APending Publication Date: 2025-02-11HARBIN UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411529686.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The polyetherimide-based energy storage composite medium has large dielectric loss and poor energy storage performance under high temperature conditions, and the introduction of many traps will lead to deterioration of the long-term durability characteristics of the medium.

Method used

By introducing 4-N,N-dimethylaminophenylboric acid with scattering electron characteristics and tetrafluorotetracyanoquinolinedimethylantimethylantimethylantimethylantimethylantimethylantimethylantimethylantimethylantimethylantimethylantimethylantichloride with electron trapping characteristics, a bifunctional symmetric three-layer structure composite medium is constructed to regulate the scattering electron layer and Capture the position and thickness of the electron layer to reduce conductivity and increase the breakdown field strength.

Benefits of technology

Under the conditions of 150°C and 620kV/mm, the charged and discharge efficiency of the prepared composite medium was 93.26%, and the discharge energy density reached 6.14J/cm3, which significantly improved the energy storage performance and maintained the long-term durability characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410010A_ABST
    Figure CN119410010A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-layer structure polyetherimide energy storage composite dielectric film and application thereof, and belongs to the technical field of energy storage dielectric materials and preparation thereof. The invention aims to solve the problems of large high-temperature dielectric loss and poor energy storage performance of the existing polyetherimide-based energy storage composite medium. The multi-layer structure polyetherimide energy storage composite dielectric film is of a three-layer structure and is composed of a scattering electron layer and a capturing electron layer. According to one structure, two surface layers are scattering electron layers, and a middle layer is a capturing electron layer; in the other structure, two surface layers are capture electron layers, and the middle layer is a scattering electron layer; the scattering electron layer is formed by compounding polyetherimide and 4-N, N-dimethylamino phenylboronic acid; and the electron capture layer is formed by compounding polyetherimide and tetrafluoro (4-cyano) quinoline dimethane. The preparation method belongs to an all-organic system, is suitable for large-scale production, and provides a new research and development thought for large-scale production of high-temperature and high-field energy storage all-organic composite films used for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of energy storage dielectric materials and preparation thereof. Background Art

[0002] The rapid development of UHV DC transmission, new energy power generation, electric vehicles and other fields has created an important demand for high-efficiency, low-cost and environmentally friendly energy storage technology. Polymer-based dielectric capacitors have the characteristics of high power density, large open circuit voltage and good safety, and have become an important energy storage device. However, under complex working conditions such as strong electric fields and high temperatures, dielectric capacitors still face the problem of deterioration of energy storage performance. The reason is that under extreme conditions, the insulation of the energy storage dielectric material decreases and the conductivity loss increases.

[0003] The molecular structure of polyetherimide (PEI) contains imide groups. The bond energy of the carbon-nitrogen bond and the carbon-oxygen bond in the group is high, and it is not easy to break at high temperature. They all have more aromatic ring structures and strong rigidity. Therefore, they have higher temperature resistance and show great potential in the selection of high-temperature energy storage dielectrics. Although PEI has good temperature resistance, the conductivity loss increases sharply at 150°C, and the energy storage performance deteriorates seriously. Current research has confirmed that the introduction of traps is an effective modification strategy to improve energy storage performance, especially the method of doping organic molecular semiconductors has shown great potential. However, the introduction of more traps will lead to the accumulation of space charge in the medium, and cause electric field distortion, which will deteriorate the long-term durability of the dielectric. Therefore, it is urgent to develop high-performance energy storage dielectric materials suitable for complex working conditions and long-term durability under the premise of reducing the amount of traps introduced. Summary of the invention

[0004] The purpose of the present invention is to solve the problems of large high-temperature dielectric loss and poor energy storage performance of existing polyetherimide-based energy storage composite media, and to provide a multilayer polyetherimide energy storage composite medium film and its application.

[0005] The present invention introduces 4-N,N-dimethylaminophenylboronic acid (4-NB), a filler with scattering electron properties, into polyetherimide (PEI) as a scattering electron layer, and introduces tetrafluorotetracyanoquinodimethane (F4TCNQ), a filler with capturing electron properties, into polyetherimide (PEI) as a capturing electron layer. By regulating the position and thickness of the scattering electron layer and the capturing electron layer, a dual-functional symmetrical three-layer structure composite medium (multilayer structure polyetherimide energy storage composite medium film) with scattering electrons and captured electrons is constructed. The scattering electron layer and the capturing electron layer effectively hinder the injection and transmission of carriers, reduce the conduction current, and the strong interaction force between the dual functional layers is also conducive to improving the breakdown field strength, and ultimately improves the energy storage performance of the composite medium. The results show that the prepared composite medium has a discharge energy density of 6.14 J / cm at 150°C, 620 kV / mm, and a charge and discharge efficiency of 93.26%. 3 .

[0006] A multilayer polyetherimide energy storage composite dielectric film is a three-layer structure, and is composed of a scattering electron layer and a capturing electron layer; one structure is that the two surface layers are scattering electron layers, and the middle layer is a capturing electron layer; the other structure is that the two surface layers are capturing electron layers, and the middle layer is a scattering electron layer; the scattering electron layer is composited by polyetherimide and 4-N,N-dimethylaminophenylboronic acid; the capturing electron layer is composited by polyetherimide and tetrafluorotetracyanoquinoline dimethane.

[0007] The two surface layers of the multilayer structured polyetherimide energy storage composite dielectric film are scattering electron layers, and the middle layer is a capturing electron layer. The preparation method thereof is specifically completed according to the following steps:

[0008] 1. dissolving polyetherimide and 4-N,N-dimethylaminophenylboronic acid in N-methylpyrrolidone, and then performing vacuum defoaming treatment to obtain a bubble-free 4-NB / PEI mixed solution;

[0009] 2. Dissolving polyetherimide and tetrafluorotetracyanoquinoline dimethane in N-methylpyrrolidone, and then performing vacuum defoaming treatment to obtain a bubble-free F4TCNQ / PEI mixed solution;

[0010] 3. Scrape the bubble-free 4-NB / PEI mixed solution on the substrate and dry it to form a lower surface composite film, which is the scattering electron layer;

[0011] Fourth, the bubble-free F4TCNQ / PEI mixed solution is scraped on the lower surface composite film, and then dried to form an intermediate composite film, which is the electron capture layer;

[0012] 5. The bubble-free 4-NB / PEI mixed solution is scraped on the middle layer composite film, and then dried to form an upper surface composite film, which is the scattering electron layer; a three-layer composite dielectric film is constructed, which is a multi-layer structure polyetherimide energy storage composite dielectric film.

[0013] A multi-layered polyetherimide energy storage composite dielectric film has two surface layers as electron capture layers and a middle layer as an electron scattering layer. The preparation method is specifically completed according to the following steps:

[0014] 1. dissolving polyetherimide and 4-N,N-dimethylaminophenylboronic acid in N-methylpyrrolidone, and then performing vacuum defoaming treatment to obtain a bubble-free 4-NB / PEI mixed solution;

[0015] 2. Dissolving polyetherimide and tetrafluorotetracyanoquinoline dimethane in N-methylpyrrolidone, and then performing vacuum defoaming treatment to obtain a bubble-free F4TCNQ / PEI mixed solution;

[0016] 3. Scrape the bubble-free F4TCNQ / PEI mixed solution on the substrate and dry it to form a lower surface composite film, which is the electron capture layer;

[0017] Fourth, the bubble-free 4-NB / PEI mixed solution is scraped on the lower surface composite film, and then dried to form an intermediate composite film, which is the scattering electron layer;

[0018] 5. The bubble-free F4TCNQ / PEI mixed solution is scraped on the middle layer composite film, and then dried to form an upper surface composite film, which is the electron capture layer; a three-layer composite dielectric film is constructed, which is a multi-layer structure polyetherimide energy storage composite dielectric film.

[0019] A multilayered polyetherimide energy storage composite dielectric film is used as a dielectric material of a dielectric capacitor; the dielectric capacitor is used for a high-voltage flexible direct current transmission converter valve, a new energy power generation filter or a new energy vehicle electric vehicle inverter.

[0020] A multilayer polyetherimide energy storage composite dielectric film is used in high temperature and high field conditions for electrical energy storage devices. It can achieve a discharge energy density of 6.14 J / cm at a charge and discharge efficiency of 93.26% at 150°C and 620 kV / mm. 3 .

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The present invention introduces the molecular semiconductor 4-N, N-dimethylaminophenylboronic acid with scattering electrons into the polyetherimide polymer to construct a scattering electron layer (4-NB / PEI), and introduces the molecular semiconductor tetrafluorotetracyanoquinoline dimethane with captured electrons into the polyetherimide polymer to construct a captured electron layer (F4TCNQ / PEI). The 4-NB / PEI or F4TCNQ / PEI layer is used as the surface layer, and another type of composite medium is used as the middle layer to construct a double-functional layer three-layer symmetrical polyetherimide film. The multilayer structure with the functions of scattering electron layer and captured electron layer, under the premise of reducing the amount of traps, synergistically achieves the suppression of low-energy electron injection and high-energy electron transmission, and shows good potential in reducing carrier accumulation. The final example results show that the all-organic energy storage composite medium prepared by the present invention has a discharge energy density of 6.14 J / cm at 150°C, 620 kV / mm and a charge and discharge efficiency of 93.26%. 3 ;

[0023] Second, the present invention introduces 4-N,N-dimethylaminophenylboronic acid with electron scattering properties into the polyetherimide polymer. The introduced small molecules have a high proportion of negative surface electrostatic potential, which can have a strong scattering effect on electrons, reduce the collision ionization of electrons in the electron transmission path, weaken the energy of electrons, and reduce the injection and transmission of electrons;

[0024] 3. The present invention introduces tetrafluorotetracyanoquinodimethane with the property of capturing electron scattering into the polyetherimide polymer. The introduced small molecule has a high proportion of positive surface electrostatic potential, which can strongly capture electrons and avoid high-energy electron transmission.

[0025] Fourth, the multilayer structure polyetherimide energy storage composite dielectric film prepared by the present invention can utilize the dual functions of scattering and capturing electrons of its multilayer structure to suppress low-energy electron injection and inhibit high-energy electron transmission in the body; and utilize the electrostatic attraction between the dual-functional layers to make the interface have a strong force, which can improve the stability of the composite medium; the contact between the interlayer fillers will redistribute the electrostatic potential of the fillers, enhance the intermolecular force, and enhance the ability to resist the impact of high-energy electrons, thereby reducing the energy loss of the composite medium, solving the problems of poor high-temperature energy storage characteristics and high dielectric loss of existing polyetherimide;

[0026] 5. The present invention belongs to a fully organic system, which is suitable for large-scale production, and the multilayer structure is a symmetrical structure, which can reduce the difficulty of production and provide a new research and development idea for the large-scale production of high-temperature, high-field and long-term energy storage fully organic composite film preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1(a) is the surface electrostatic potential cloud map and potential statistics diagram of 4-N,N-dimethylaminophenylboronic acid, (b) is the surface electrostatic potential cloud map and potential statistics diagram of tetrafluorotetracyanoquinolinodimethane;

[0028] Figure 2 (a) is the cross-sectional morphology and element distribution diagram of FNF-3 film, (b) is the cross-sectional morphology and element distribution diagram of FNF-4 film, (c) is the cross-sectional morphology and element distribution diagram of FNF-5 film, (d) is the cross-sectional morphology and element distribution diagram of NFN-3 film, (e) is the cross-sectional morphology and element distribution diagram of NFN-4 film, (f) is the cross-sectional morphology and element distribution diagram of NFN-5 film;

[0029] Figure 3 (a) is the XRD spectrum of the composite medium obtained in different embodiments, and (b) is the XRD spectrum of 4-N,N-dimethylaminophenylboronic acid, tetrafluorotetracyanoquinolinodimethane and comparative example;

[0030] Figure 4 (a) is an infrared spectrum of the composite medium obtained in different embodiments, and (b) is an infrared spectrum of 4-N,N-dimethylaminophenylboronic acid, tetrafluorotetracyanoquinolinodimethane and a comparative example;

[0031] Figure 5 (a) is a curve showing the change of dielectric constant and dielectric loss with frequency at 150°C for the composite medium obtained in different embodiments, and (b) is a curve showing the change of dielectric constant and dielectric loss with frequency at 150°C for the comparative example;

[0032] Figure 6 (a) is a Weibull distribution diagram of the breakdown field strength of the composite medium obtained in different embodiments at 150°C, and (b) is a Weibull distribution diagram of the breakdown field strength of the comparative example at 150°C;

[0033] Figure 7 (a) is a graph showing the change of the conductivity current with the electric field strength at 150°C for the composite medium obtained in different embodiments, and (b) is a graph showing the change of the conductivity current with the electric field strength at 150°C for the comparative example;

[0034] Figure 8 (a) is a diagram showing the energy storage characteristics of the composite media obtained in different embodiments at 150°C, and (b) is a diagram showing the energy storage characteristics of the comparative example at 150°C;

[0035] Fig. 9(a) is a schematic diagram of the interface charge of a thin film with a 3 μm thick scattering electron layer as the surface layer and a captured electron layer as the middle layer, (b) is a schematic diagram of the interface charge of a thin film with a 4 μm thick scattering electron layer as the surface layer and a captured electron layer as the middle layer, (c) is a schematic diagram of the interface charge of a thin film with a 5 μm thick scattering electron layer as the surface layer and a captured electron layer as the middle layer, (d) is a schematic diagram of the interface charge of a thin film with a 5 μm thick captured electron layer as the surface layer and a scattering electron layer as the middle layer;

[0036] Fig.10 (a) is the AC box model diagram of 4-N,N-dimethylaminophenylboronic acid and tetrafluorotetracyanoquinoline dimethane, and (b) is the interaction energy data diagram of 4-N,N-dimethylaminophenylboronic acid and tetrafluorotetracyanoquinoline dimethane. DETAILED DESCRIPTION

[0037] Specific implementation method 1: This implementation method is a multi-layer polyetherimide energy storage composite dielectric film with a three-layer structure, and is composed of a scattering electron layer and a capture electron layer; one structure is that the two surface layers are scattering electron layers, and the middle layer is a capture electron layer; the other structure is that the two surface layers are capture electron layers, and the middle layer is a scattering electron layer; the scattering electron layer is composed of polyetherimide and 4-N,N-dimethylaminophenylboronic acid; the capture electron layer is composed of polyetherimide and tetrafluorotetracyanoquinoline dimethane.

[0038] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the volume ratio of 4-N,N-dimethylaminophenylboronic acid to polyetherimide in the scattering electron layer is 0.008:1; the volume ratio of tetrafluorotetracyanoquinoline dimethane to polyetherimide in the capturing electron layer is 0.006:1. The other steps are the same as those in specific embodiment 1.

[0039] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that: the thickness of the multilayer structure polyetherimide energy storage composite dielectric film is 5 μm to 13 μm; the ratio of the thickness of a single surface layer to the total thickness of the multilayer structure polyetherimide energy storage composite dielectric film is (3 to 5): 13. The other steps are the same as those of specific embodiment 1 or 2.

[0040] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the two surface layers of the multilayer structure polyetherimide energy storage composite dielectric film are scattering electron layers, and the middle layer is a capture electron layer. The preparation method is specifically completed according to the following steps:

[0041] 1. dissolving polyetherimide and 4-N,N-dimethylaminophenylboronic acid in N-methylpyrrolidone, and then performing vacuum defoaming treatment to obtain a bubble-free 4-NB / PEI mixed solution;

[0042] 2. Dissolving polyetherimide and tetrafluorotetracyanoquinoline dimethane in N-methylpyrrolidone, and then performing vacuum defoaming treatment to obtain a bubble-free F4TCNQ / PEI mixed solution;

[0043] 3. Scrape the bubble-free 4-NB / PEI mixed solution on the substrate and dry it to form a lower surface composite film, which is the scattering electron layer;

[0044] Fourth, the bubble-free F4TCNQ / PEI mixed solution is scraped on the lower surface composite film, and then dried to form an intermediate composite film, which is the electron capture layer;

[0045] Fifth, the bubble-free 4-NB / PEI mixed solution is scraped on the middle layer composite film, and then dried to form an upper surface composite film, which is the scattering electron layer; a three-layer composite dielectric film is constructed, which is a multi-layer structure polyetherimide energy storage composite dielectric film. The other steps are the same as the specific embodiments one to three.

[0046] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the two surface layers of the multilayer structure polyetherimide energy storage composite dielectric film are electron capture layers, and the middle layer is an electron scattering layer. The preparation method is specifically completed according to the following steps:

[0047] 1. dissolving polyetherimide and 4-N,N-dimethylaminophenylboronic acid in N-methylpyrrolidone, and then performing vacuum defoaming treatment to obtain a bubble-free 4-NB / PEI mixed solution;

[0048] 2. Dissolving polyetherimide and tetrafluorotetracyanoquinoline dimethane in N-methylpyrrolidone, and then performing vacuum defoaming treatment to obtain a bubble-free F4TCNQ / PEI mixed solution;

[0049] 3. Scrape the bubble-free F4TCNQ / PEI mixed solution on the substrate and dry it to form a lower surface composite film, which is the electron capture layer;

[0050] Fourth, the bubble-free 4-NB / PEI mixed solution is scraped on the lower surface composite film, and then dried to form an intermediate composite film, which is the scattering electron layer;

[0051] Fifth, the bubble-free F4TCNQ / PEI mixed solution is scraped on the middle layer composite film, and then dried to form an upper surface composite film, which is the electron capture layer; a three-layer composite dielectric film is constructed, which is a multi-layer structure polyetherimide energy storage composite dielectric film. The other steps are the same as the specific embodiments one to four.

[0052] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: in step 1, the volume ratio of 4-N, N-dimethylaminophenylboronic acid to polyetherimide is 0.008:1; in step 1, the volume ratio of the total mass of polyetherimide and 4-N, N-dimethylaminophenylboronic acid to N-methylpyrrolidone is (0.15g-0.18g):1mL; in step 2, the volume ratio of tetrafluorotetracyanoquinoline dimethane to polyetherimide is 0.006:1; in step 2, the volume ratio of the total mass of polyetherimide and tetrafluorotetracyanoquinoline dimethane to N-methylpyrrolidone is (0.15g-0.18g):1mL. The other steps are the same as specific embodiments 1 to 5.

[0053] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the vacuum defoaming treatment method described in step 1 and step 2 is: gradient vacuum treatment is adopted, firstly, the mixture is allowed to stand for 5 min to 15 min in a vacuum environment of 500 mbar and 30° C., then for 5 min to 15 min in a vacuum environment of 100 mbar and 30° C., and finally for 5 min to 15 min in a vacuum environment of 10 mbar and 30° C. The other steps are the same as those of specific embodiments 1 to 6.

[0054] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that the drying method described in step three, step four and step five is:

[0055] ①. In an environment with a relative humidity of 40%, keep warm at 70℃ for 4 hours, and then keep warm at 120℃ for 2 hours;

[0056] ② In an environment with a relative humidity of 30%, keep warm at 150℃ for 2 hours, and then keep warm at 200℃ for 2 hours;

[0057] ③. In an environment with a relative humidity of 20%, keep warm for 4 hours at 200℃ in a nitrogen atmosphere;

[0058] ④. Cool the film to room temperature in a nitrogen atmosphere, and control the nitrogen flow along the coating direction. The other steps are the same as those in Specific Embodiments 1 to 7.

[0059] Specific embodiment nine: This embodiment is a multilayer structure polyetherimide energy storage composite dielectric film used as a dielectric material of a dielectric capacitor; the dielectric capacitor is used for a high-voltage flexible DC transmission converter valve, a new energy power generation filter or a new energy vehicle electric vehicle inverter.

[0060] Specific embodiment 10: This embodiment is a multilayer structure polyetherimide energy storage composite dielectric film for use in an energy storage device under high temperature and high field conditions, capable of achieving a discharge energy density of 6.14 J / cm at a charge and discharge efficiency of 93.26% at 150°C and 620 kV / mm. 3 .

[0061] The following examples are used to verify the beneficial effects of the present invention:

[0062] Example 1: A multi-layered polyetherimide energy storage composite dielectric film has two surface layers as electron capture layers and a middle layer as an electron scattering layer. The preparation method is specifically completed according to the following steps:

[0063] 1. At 60℃ and stirring speed of 300r / min, PolyK 1000 polyetherimide and 4-N,N-dimethylaminophenylboronic acid were dissolved in N-methylpyrrolidone, and then vacuum defoamed to obtain a bubble-free 4-NB / PEI mixed solution;

[0064] In step 1, the volume ratio of 4-N,N-dimethylaminophenylboronic acid to polyetherimide is 0.008:1;

[0065] In step 1, the volume ratio of the total mass of polyetherimide and 4-N,N-dimethylaminophenylboronic acid to N-methylpyrrolidone is 0.16 g:1 mL;

[0066] 2. Dissolve polyetherimide and tetrafluorotetracyanoquinoline dimethane in N-methylpyrrolidone at 60°C and a stirring speed of 300 r / min, and then perform vacuum defoaming treatment to obtain a bubble-free F4TCNQ / PEI mixed solution;

[0067] In step 2, the volume ratio of tetrafluorotetracyanoquinolinodimethane to polyetherimide is 0.006:1;

[0068] The volume ratio of the total mass of polyetherimide and tetrafluorotetracyanoquinolinodimethane to N-methylpyrrolidone in step 2 is 0.16 g:1 mL;

[0069] 3. Pour the bubble-free 4-NB / PEI mixed solution evenly on a clean flat glass plate, raise the coating knife to a height of 4.5 μm, scrape horizontally at a speed of 5 cm / s, and then dry it to form a 3 μm thick and densely structured lower surface composite film, which is the scattering electron layer;

[0070] Fourth, pour the bubble-free F4TCNQ / PEI mixed solution evenly on the lower surface composite film, raise the coating knife to a height of 10.5μm, scrape horizontally at a speed of 5cm / s, and then dry it to form a 7μm thick and densely structured middle layer composite film, which is the electron capture layer;

[0071] 5. Pour the bubble-free 4-NB / PEI mixed solution evenly on the middle layer composite film, raise the coating knife to a height of 4.5 μm, scrape horizontally at a speed of 5 cm / s, and then dry it to form a 3 μm thick and dense upper surface composite film, which is the scattering electron layer; construct a 13 μm thick and dense three-layer composite dielectric film, which is a multilayer polyetherimide energy storage composite dielectric film (denoted as NFN-3);

[0072] The vacuum defoaming treatment method described in step 1 and step 2 is: using gradient vacuum treatment, first standing for 10 minutes in a vacuum environment of 500 mbar and 30°C, then standing for 10 minutes in a vacuum environment of 100 mbar and 30°C, and finally standing for 10 minutes in a vacuum environment of 10 mbar and 30°C;

[0073] The drying method described in step 3, step 4 and step 5 is:

[0074] ①. In an environment with a relative humidity of 40%, keep warm at 70℃ for 4 hours, and then keep warm at 120℃ for 2 hours;

[0075] ② In an environment with a relative humidity of 30%, keep warm at 150℃ for 2 hours, and then keep warm at 200℃ for 2 hours;

[0076] ③. In an environment with a relative humidity of 20%, keep warm for 4 hours at 200℃ in a nitrogen atmosphere;

[0077] ④. Place the film in a nitrogen atmosphere and cool it to room temperature, and control the nitrogen flow along the coating direction.

[0078] Example 2: The difference between this example and Example 1 is that in step 3, the bubble-free 4-NB / PEI mixed solution is evenly poured on a clean flat glass plate, the coating knife is raised to a height of 6 μm, horizontally scraped at a speed of 5 cm / s, and then dried to form a lower surface composite film with a thickness of 4 μm and a dense structure, which is the scattering electron layer; in step 4, the bubble-free F4TCNQ / PEI mixed solution is evenly poured on the lower surface composite film, the coating knife is raised to a height of 6.5 μm, horizontally scraped at a speed of 5 cm / s, and then dried. Dry treatment was performed to form a dense middle layer composite film with a thickness of 5 μm, which was the electron capture layer; in step five, the bubble-free 4-NB / PEI mixed solution was evenly poured on the middle layer composite film, the coating knife was raised to a height of 6 μm, and horizontally scraped at a speed of 5 cm / s, and then dried to form a dense upper surface composite film with a thickness of 4 μm, which was the scattering electron layer; a three-layer composite dielectric film with a thickness of 13 μm and a dense structure was constructed, which was a multilayer polyetherimide energy storage composite dielectric film (denoted as NFN-4).

[0079] Example 3: The difference between this example and Example 1 is that in step 3, the bubble-free 4-NB / PEI mixed solution is evenly poured on a clean flat glass plate, the coating knife is raised to a height of 6.5 μm, horizontally scraped at a speed of 5 cm / s, and then dried to form a lower surface composite film with a thickness of 5 μm and a dense structure, which is the scattering electron layer; in step 4, the bubble-free F4TCNQ / PEI mixed solution is evenly poured on the lower surface composite film, the coating knife is raised to a height of 4.5 μm, horizontally scraped at a speed of 5 cm / s, and then dried. Dry treatment was performed to form a dense middle layer composite film with a thickness of 3 μm, which was the electron capture layer; in step five, the bubble-free 4-NB / PEI mixed solution was evenly poured on the middle layer composite film, the coating knife was raised to a height of 6.5 μm, and horizontally scraped at a speed of 5 cm / s, and then dried to form a dense upper surface composite film with a thickness of 5 μm, which was the scattering electron layer; a three-layer composite dielectric film with a thickness of 13 μm and a dense structure was constructed, which was a multilayer polyetherimide energy storage composite dielectric film (denoted as NFN-5).

[0080] Example 4: A multi-layered polyetherimide energy storage composite dielectric film has two surface layers as electron capture layers and a middle layer as an electron scattering layer. The preparation method is specifically completed according to the following steps:

[0081] 1. At 60℃ and stirring speed of 300r / min, PolyK 1000 polyetherimide and 4-N,N-dimethylaminophenylboronic acid were completely dissolved in N-methylpyrrolidone, and then vacuum defoamed to obtain a bubble-free 4-NB / PEI mixed solution;

[0082] In step 1, the volume ratio of 4-N,N-dimethylaminophenylboronic acid to polyetherimide is 0.008:1;

[0083] In step 1, the volume ratio of the total mass of polyetherimide and 4-N,N-dimethylaminophenylboronic acid to N-methylpyrrolidone is 0.16 g:1 mL;

[0084] 2. Under the conditions of 60°C and a stirring speed of 300 r / min, polyetherimide and tetrafluorotetracyanoquinoline dimethane are completely dissolved in N-methylpyrrolidone, and then vacuum defoaming treatment is performed to obtain a bubble-free F4TCNQ / PEI mixed solution;

[0085] In step 2, the volume ratio of tetrafluorotetracyanoquinolinodimethane to polyetherimide is 0.006:1;

[0086] The volume ratio of the total mass of polyetherimide and tetrafluorotetracyanoquinolinodimethane to N-methylpyrrolidone in step 2 is 0.16 g:1 mL;

[0087] 3. Pour the bubble-free F4TCNQ / PEI mixed solution evenly on a clean and flat glass plate, raise the coating knife to a height of 4.5μm, scrape horizontally at a speed of 5cm / s, and then dry it to form a 3μm thick and densely structured lower surface composite film, which is the electron capture layer;

[0088] Fourth, pour the bubble-free 4-NB / PEI mixed solution evenly on the lower surface composite film, raise the coating knife to a height of 10.5μm, scrape horizontally at a speed of 5cm / s, and then dry it to form a 7μm thick and densely structured middle layer composite film, which is the scattering electron layer;

[0089] 5. Pour the bubble-free F4TCNQ / PEI mixed solution evenly on the middle layer composite film, raise the coating knife to a height of 4.5 μm, scrape horizontally at a speed of 5 cm / s, and then dry it to form a 3 μm thick and dense upper surface composite film, which is the electron capture layer; construct a 13 μm thick and dense three-layer composite dielectric film, which is a multilayer polyetherimide energy storage composite dielectric film (denoted as FNF-3);

[0090] The vacuum defoaming treatment method described in step 1 and step 2 is: using gradient vacuum treatment, first standing for 10 minutes in a vacuum environment of 500 mbar and 30°C, then standing for 10 minutes in a vacuum environment of 100 mbar and 30°C, and finally standing for 10 minutes in a vacuum environment of 10 mbar and 30°C;

[0091] The drying method described in step 3, step 4 and step 5 is:

[0092] ①. In an environment with a relative humidity of 40%, keep warm at 70℃ for 4 hours, and then keep warm at 120℃ for 2 hours;

[0093] ② In an environment with a relative humidity of 30%, keep warm at 150℃ for 2 hours, and then keep warm at 200℃ for 2 hours;

[0094] ③. In an environment with a relative humidity of 20%, keep warm for 4 hours at 200℃ in a nitrogen atmosphere;

[0095] ④. Place the film in a nitrogen atmosphere and cool it to room temperature, and control the nitrogen flow along the coating direction.

[0096] Example 5: The difference between this example and Example 4 is that in step 3, the bubble-free F4TCNQ / PEI mixed solution is evenly poured on a clean flat glass plate, the coating knife is raised to a height of 6 μm, and horizontally scraped at a speed of 5 cm / s, and then dried to form a lower surface composite film with a thickness of 4 μm and a dense structure, which is the electron capture layer; in step 4, the bubble-free 4-NB / PEI mixed solution is evenly poured on the lower surface composite film, the coating knife is raised to a height of 6.5 μm, and horizontally scraped at a speed of 5 cm / s, and then dried. Processing, forming a 5μm thick dense structure of the middle layer composite film, that is, the scattering electron layer; in step 5, the bubble-free F4TCNQ / PEI mixed solution is evenly poured on the middle layer composite film, the coating knife is raised to a height of 6μm, horizontally scraped at a speed of 5cm / s, and then dried to form a 4μm thick dense structure of the upper surface composite film, that is, the capture electron layer; a 13μm thick dense structure of the three-layer composite dielectric film is constructed, that is, a multilayer structure polyetherimide energy storage composite dielectric film (referred to as FNF-4). The other steps and parameters are the same as those in Example 4.

[0097] Example 6: The difference between this example and Example 4 is that in step 3, the bubble-free F4TCNQ / PEI mixed solution is evenly poured on a clean flat glass plate, the coating knife is raised to a height of 6.5 μm, horizontally scraped at a speed of 5 cm / s, and then dried to form a lower surface composite film with a thickness of 5 μm and a dense structure, which is the electron capture layer; in step 4, the bubble-free 4-NB / PEI mixed solution is evenly poured on the lower surface composite film, the coating knife is raised to a height of 4.5 μm, horizontally scraped at a speed of 5 cm / s, and then dried Processing, forming a 3μm thick dense structure of the middle layer composite film, that is, the scattering electron layer; in step 5, the bubble-free F4TCNQ / PEI mixed solution is evenly poured on the middle layer composite film, the coating knife is raised to a height of 6.5μm, horizontally scraped at a speed of 5cm / s, and then dried to form a 5μm thick dense structure of the upper surface composite film, that is, the capture electron layer; a 13μm thick dense structure of the three-layer composite dielectric film is constructed, that is, a multilayer structure polyetherimide energy storage composite dielectric film (referred to as FNF-5). The other steps and parameters are the same as those in Example 4.

[0098] Comparative Example 1: The preparation method of the PEI dielectric film is specifically completed according to the following steps:

[0099] 1. At 60℃ and stirring speed of 300r / min, PolyK Ultem 1000 polyetherimide was completely dissolved in N-methylpyrrolidone, and then vacuum defoamed to obtain a bubble-free PEI solution;

[0100] The volume ratio of the polyetherimide mass to N-methylpyrrolidone in step 1 is 0.16 g:1 mL;

[0101] 2. Pour the bubble-free PEI solution evenly onto a clean flat glass plate, raise the coating knife to a height of 19.5 μm, scrape horizontally at a speed of 5 cm / s, and then dry to form a 13 μm thick and dense PEI dielectric film (denoted as PEI);

[0102] The vacuum degassing treatment method described in step 1 is: using gradient vacuum treatment, first standing in a vacuum environment of 500 mbar and 30°C for 10 minutes, then standing in a vacuum environment of 100 mbar and 30°C for 10 minutes, and finally standing in a vacuum environment of 10 mbar and 30°C for 10 minutes;

[0103] The drying method described in step 2 is:

[0104] ①. In an environment with a relative humidity of 40%, keep warm at 70℃ for 4 hours, and then keep warm at 120℃ for 2 hours;

[0105] ② In an environment with a relative humidity of 30%, keep warm at 150℃ for 2 hours, and then keep warm at 200℃ for 2 hours;

[0106] ③. In an environment with a relative humidity of 20%, keep warm for 4 hours at 200℃ in a nitrogen atmosphere;

[0107] ④. Place the film in a nitrogen atmosphere and cool it to room temperature, and control the nitrogen flow along the coating direction.

[0108] Comparative Example 2: The preparation method of F4TCNQ / PEI composite dielectric film is specifically completed according to the following steps:

[0109] 1. At 60℃ and stirring speed of 300r / min, PolyK 1000 polyetherimide and tetrafluorotetracyanoquinoline dimethane were completely dissolved in N-methylpyrrolidone, and then vacuum defoamed to obtain a bubble-free F4TCNQ / PEI mixed solution;

[0110] In step 1, the volume ratio of tetrafluorotetracyanoquinolinodimethane to polyetherimide is 0.006:1;

[0111] The volume ratio of the total mass of polyetherimide and tetrafluorotetracyanoquinolinodimethane to N-methylpyrrolidone in step 1 is 0.16 g:1 mL;

[0112] 2. Pour the bubble-free F4TCNQ / PEI mixed solution evenly on a clean flat glass plate, raise the coating knife to a height of 19.5 μm, scrape horizontally at a speed of 5 cm / s, and then dry it to form a 13 μm thick and dense F4TCNQ / PEI composite dielectric film (denoted as F 0.6 );

[0113] The vacuum degassing treatment method described in step 1 is: using gradient vacuum treatment, first standing in a vacuum environment of 500 mbar and 30°C for 10 minutes, then standing in a vacuum environment of 100 mbar and 30°C for 10 minutes, and finally standing in a vacuum environment of 10 mbar and 30°C for 10 minutes;

[0114] The drying method described in step 2 is:

[0115] ①. In an environment with a relative humidity of 40%, keep warm at 70℃ for 4 hours, and then keep warm at 120℃ for 2 hours;

[0116] ② In an environment with a relative humidity of 30%, keep warm at 150℃ for 2 hours, and then keep warm at 200℃ for 2 hours;

[0117] ③. In an environment with a relative humidity of 20%, keep warm for 4 hours at 200℃ in a nitrogen atmosphere;

[0118] ④. Place the film in a nitrogen atmosphere and cool it to room temperature, and control the nitrogen flow along the coating direction.

[0119] Comparative Example 3: The preparation method of 4-NB / PEI composite dielectric film is specifically completed according to the following steps:

[0120] 1. At 60℃ and stirring speed of 300r / min, PolyK 1000 polyetherimide and 4-N,N-dimethylaminophenylboronic acid were completely dissolved in N-methylpyrrolidone, and then vacuum defoamed to obtain a bubble-free 4-NB / PEI mixed solution;

[0121] In step 1, the volume ratio of 4-N,N-dimethylaminophenylboronic acid to polyetherimide is 0.008:1;

[0122] In step 1, the volume ratio of the total mass of polyetherimide and 4-N,N-dimethylaminophenylboronic acid to N-methylpyrrolidone is 0.16 g:1 mL;

[0123] 2. Pour the bubble-free 4-NB / PEI mixed solution evenly onto a clean flat glass plate, raise the coating knife to a height of 19.5 μm, scrape horizontally at a speed of 5 cm / s, and then dry to form a 13 μm thick and dense 4-NB / PEI composite dielectric film (denoted as N 0.8 );

[0124] The vacuum degassing treatment method described in step 1 is: using gradient vacuum treatment, first standing in a vacuum environment of 500 mbar and 30°C for 10 minutes, then standing in a vacuum environment of 100 mbar and 30°C for 10 minutes, and finally standing in a vacuum environment of 10 mbar and 30°C for 10 minutes;

[0125] The drying method described in step 2 is:

[0126] ①. In an environment with a relative humidity of 40%, keep warm at 70℃ for 4 hours, and then keep warm at 120℃ for 2 hours;

[0127] ② In an environment with a relative humidity of 30%, keep warm at 150℃ for 2 hours, and then keep warm at 200℃ for 2 hours;

[0128] ③. In an environment with a relative humidity of 20%, keep warm for 4 hours at 200℃ in a nitrogen atmosphere;

[0129] ④. Place the film in a nitrogen atmosphere and cool it to room temperature, and control the nitrogen flow along the coating direction.

[0130] The structure and performance of the composite media obtained in Examples 1-6 and Comparative Examples 1-3 were characterized, and the results are as follows:

[0131] Figure 1 (a) is the surface electrostatic potential cloud map and potential statistics diagram of 4-N,N-dimethylaminophenylboronic acid, (b) is the surface electrostatic potential cloud map and potential statistics diagram of tetrafluorotetracyanoquinolinodimethane;

[0132] Depend on Figure 1 It can be seen that the electrostatic potential near the tetrafluorophenyl and cyanide groups in F4TCNQ is positive, indicating that there is a strong electron affinity at this position. The electrostatic potential of 4-NB near the boric acid and benzene ring is negative, showing obvious scattered electron characteristics. The area difference of the surface potential distribution of the two fillers is also large. The positive electrostatic potential area of ​​F4TCNQ accounts for a high proportion, which can reach 63.78%, and has a proportion of up to 32.72% in the strong positive potential range (20-45kcal / mol), indicating that the filler as a whole exhibits the characteristic of capturing electrons. The electrostatic potential area of ​​4-NB is high in the range of -30-0kcal / mol, which can reach 60%. The potential values ​​of the areas with a high positive electrostatic potential are relatively low, so the filler as a whole exhibits scattered electron characteristics.

[0133] Figure 2 (a) is the cross-sectional morphology and element distribution diagram of FNF-3 film, (b) is the cross-sectional morphology and element distribution diagram of FNF-4 film, (c) is the cross-sectional morphology and element distribution diagram of FNF-5 film, (d) is the cross-sectional morphology and element distribution diagram of NFN-3 film, (e) is the cross-sectional morphology and element distribution diagram of NFN-4 film, (f) is the cross-sectional morphology and element distribution diagram of NFN-5 film;

[0134] Depend on Figure 2It can be seen that the cross section of the multilayer composite medium is smooth, free of impurities, the overall thickness is maintained at 13μm, and the thickness of the functional layer is consistent with the designed thickness of the experimental plan, with a small error, indicating that the coating process can achieve the construction of a multilayer modified structure. From the cross-sectional view of the composite medium, it can be seen that when the surface thickness is small, the interface is clearer, and as the surface thickness increases, the interface clarity decreases. This may be due to the uneven expansion of the medium with different thickness layers during the drying process, resulting in a more obvious interface. It may also be due to the uneven stress distribution of the multilayer medium with uneven thickness distribution during the brittle fracture test before the SEM experiment, resulting in cracks in the interface area and a more obvious interface. The energy spectrum analysis was used to characterize the distribution of the element composition of the multilayer structure, the B element was used to characterize the distribution of 4-NB, and the F element was used to characterize the distribution of F4TCNQ. Taking NFN-4 as an example, a large amount of B elements are distributed in the surface layer, and a large amount of F elements are distributed in the middle layer, proving that the constructed multilayer structure is a NFN structure, and the filler distribution is in line with the design plan. There is a small amount of B element distributed in the middle layer, and a small amount of F element distributed in the surface layer. This may be due to the migration of a small amount of filler, or it may be due to the stray signal of the test instrument causing the test error.

[0135] Figure 3 (a) is the XRD spectrum of the composite medium obtained in different embodiments, and (b) is the XRD spectrum of 4-N,N-dimethylaminophenylboronic acid, tetrafluorotetracyanoquinolinodimethane and comparative example;

[0136] Depend on Figure 3 It can be seen that there are no sharp and high-intensity characteristic peaks in the composite medium, which proves that the prepared multilayer composite medium is of high purity and has no impurities introduced. Compared with pure PEI, the bun peak of the multilayer composite medium in the range of 10°-30° has shifted to the left, mainly because the introduction of 4-NB reduces the stacking of PEI molecular chains. The spectrum also shows that as the thickness of the 4-NB layer increases, the bun peak shifts to the left more, which is due to the increase in the 4-NB content in the medium.

[0137] Figure 4 (a) is an infrared spectrum of the composite medium obtained in different embodiments, and (b) is an infrared spectrum of 4-N,N-dimethylaminophenylboronic acid, tetrafluorotetracyanoquinolinodimethane and a comparative example;

[0138] Depend on Figure 4 It can be seen that at 1776cm -1 and 1712cm -1 The characteristic peak at 1367cm -1 and 725cm -1 The characteristic peak at 1240 cm -1 and 1100cm-1 The characteristic peak at 1450cm is due to the stretching vibration of COC. The composite medium FTIR does not show the characteristic peak information of F4TCNQ, but due to the 4-NB at 1450cm -1 There is a broad peak caused by the angular vibration of N(CH3)2, so the composite structure is at 1250-1500cm -1 The sharpness of the characteristic peak between the two samples decreased, which may be due to the degenerate behavior caused by the introduction of 4-NB.

[0139] Figure 5 (a) is a curve showing the change of dielectric constant and dielectric loss with frequency at 150°C for the composite medium obtained in different embodiments, and (b) is a curve showing the change of dielectric constant and dielectric loss with frequency at 150°C for the comparative example;

[0140] Depend on Figure 5 It can be seen that the relative dielectric constant of the multilayer composite medium is relatively stable in a wide frequency range, with low volatility, and the loss factor is also maintained at a low level. Among the NFN composite multilayer structures, NFN-3 has the largest relative dielectric constant, followed by NFN-4, and NFN-5 has the smallest relative dielectric constant. This is because F4TCNQ has a strong polarization ability. As the thickness of the F4TCNQ / PEI composite medium layer increases, the proportion of F4TCNQ content in the composite medium increases, so the dielectric constant shows an upward trend. The same change pattern is also shown for the FNF structure composite medium. That is, the relative dielectric constant of FNF-5 is the highest, followed by NFN-4, and the relative dielectric constant of NFN-3 is the smallest.

[0141] Figure 6 (a) is a Weibull distribution diagram of the breakdown field strength of the composite medium obtained in different embodiments at 150°C, and (b) is a Weibull distribution diagram of the breakdown field strength of the comparative example at 150°C;

[0142] Depend on Figure 6It can be seen that among the NFN structures, the characteristic breakdown field strength of NFN-4 is the highest, reaching 671.4kV / mm, NFN-5 is 663.8kV / mm, and NFN-3 is the smallest at 661.3kV / mm. With the increase of the surface thickness of 4-NB / PEI, the breakdown field strength of the composite medium increases first and then decreases. For the FNF structure, with the increase of the surface thickness of 4-NB / PEI, the breakdown field strength of the composite medium gradually increases, and the breakdown field strength of the FNF-5 structure reaches 665.2kV / mm. The breakdown field strength of the NFN structure and FNF structure composite media shows completely different rules with the change of surface thickness. For the NFN structure composite medium, when the surface thickness is small, the ability to repel electron injection is weak, and a large amount of electrons are injected into the composite medium. When the surface thickness is large, the ability of the middle layer to capture high-energy electrons is weak, and the high-energy electrons that cannot be scattered by the repelling electron layer will be accelerated in the dielectric body, resulting in a decrease in the breakdown performance of the insulating medium. For the FNF structure composite medium, the surface layer is the F4TCNQ / PEI composite medium with the property of capturing electrons, and the middle layer is the 4-NB / PEI composite medium with the property of scattering electrons. When the thickness of the F4TCNQ / PEI surface layer gradually increases, the improvement of the breakdown field strength of the composite medium is mainly attributed to the increase in traps, so the ability to capture electrons is enhanced and the ability to inhibit electron transmission is enhanced. Overall, the improvement of the breakdown performance of the NFN structure is a combination of the surface barrier advantage of the composite medium and the trap advantage in the body. The surface layer has a greater advantage in inhibiting electron injection, while the middle layer has a greater advantage in inhibiting high-energy electron transmission.

[0143] Figure 7 (a) is a graph showing the change of the conductivity current with the electric field strength at 150°C for the composite medium obtained in different embodiments, and (b) is a graph showing the change of the conductivity current with the electric field strength at 150°C for the comparative example;

[0144] As can be seen from the figure, NFN-4 has the smallest conductivity current, followed by FNF-5, and FNF-3 and FNF-4 have larger conductivity currents, but the difference is not large. However, compared with the comparative example, the conductivity current value is lower, indicating that the multilayer structure composite medium has lower conductivity loss and can reduce the generation of a large amount of heat.

[0145] Figure 8 (a) is a diagram showing the energy storage characteristics of the composite media obtained in different embodiments at 150°C, and (b) is a diagram showing the energy storage characteristics of the comparative example at 150°C;

[0146] As can be seen from the figure, for the NFN structure, as the thickness of the scattering electron surface increases, the maximum energy storage density with an efficiency of ≥90% first increases and then decreases, and the change pattern is consistent with the DC breakdown performance. NFN-4 has a strong surface layer repelling electron injection ability and a middle layer capturing high-energy electrons ability, so the performance is greatly improved. The energy storage density of NFN-4 is 6.14J / cm3 The corresponding polarization electric field is 620kV / mm, and the energy storage density is increased by 283.7% compared with pure PEI. 0.6 Improved by 26.3% compared to N 0.8 The energy storage density of FNF-5 is increased by 17.9%. In the FNF structure, the thicker the surface layer with electron-attracting properties, the better the energy storage performance. This is because the more traps are introduced, the stronger the ability to capture electrons, the stronger the dielectric strength and the less energy loss, so the energy storage density increases. However, the energy storage performance of FNF-5 can only reach 6.02 J / cm 3 , 282% higher than pure PEI, and 282% higher than F 0.6 Improved by 23.9% compared to N 0.8 The performance is improved by 15.5%. Although the performance is improved, it is still inferior to NFN-4. In addition, the FNF structure does not show a significant effect in reducing trap introduction.

[0147] Fig. 9 (a) is a schematic diagram of the interface charge of a thin film with a 3 μm thick scattering electron layer as the surface layer and a captured electron layer as the middle layer, (b) is a schematic diagram of the interface charge of a thin film with a 4 μm thick scattering electron layer as the surface layer and a captured electron layer as the middle layer, (c) is a schematic diagram of the interface charge of a thin film with a 5 μm thick scattering electron layer as the surface layer and a captured electron layer as the middle layer, (d) is a schematic diagram of the interface charge of a thin film with a 5 μm thick captured electron layer as the surface layer and a scattering electron layer as the middle layer;

[0148] As can be seen from the figure, in the NFN structure, charges of the opposite type to the charge type of the electrode plate can be formed at the interface. The self-built electric field between the interface charges is opposite to the direction of the external electric field, which can hinder the transmission of carriers in the composite medium. However, as the thickness of the surface layer increases, the interface charge decreases, and the size of the self-built electric field will change. The strength of the self-built electric field decreases with the increase of the surface thickness, and because the thickness of the intermediate layer is small, the probability of recombination of charges of different polarities increases, and the effect of inhibiting electron transmission is weakened, so there is a trend of performance degradation. For the composite medium with FNF structure, the change law of the polarity and charge amount of the interface charge with the surface thickness is consistent with that of the NPN structure, but the performance evolution law is completely opposite. This is because although the interface charge is reduced, as the thickness increases, more traps are introduced, and the capture effect of the traps occupies the dominant factor. Therefore, as the thickness of the surface layer increases, the breakdown field strength of the composite medium shows an upward trend.

[0149] Fig.10 (a) is the AC box model diagram of 4-N,N-dimethylaminophenylboronic acid and tetrafluorotetracyanoquinoline dimethane, (b) is the interaction energy data diagram of 4-N,N-dimethylaminophenylboronic acid and tetrafluorotetracyanoquinoline dimethane;

[0150] Depend on Fig.10It can be seen that the interaction energy between F4TCNQ molecules is 4062.71Ha, the interaction energy between 4-NB molecules is 611.87Ha, and the interaction energy of the whole box is 4637.65Ha, so the interlayer interaction energy is -0.06Ha, that is, -36.93kcal / mol. The interlayer interaction energy is negative, indicating that the 4-NB layer and the F4TCNQ layer have a strong mutual attraction, and the interaction force may be caused by van der Waals force, hydrogen bond, and covalent bond. Strong interaction force can increase the stability of the multilayer structure, make the interlayer bond closer, and reduce interlayer physical defects. In addition, strong interlayer force can also have a strong binding effect on electrons, hinder the transmission of electrons, and reduce conductivity loss.

[0151] In summary, the multilayer polyetherimide energy storage composite medium prepared in the present invention has lower conductivity loss, better high-temperature breakdown strength and good energy storage performance.

[0152] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A multilayer polyetherimide energy storage composite dielectric film, characterized in that The multi-layer polyetherimide energy storage composite dielectric film is a three-layer structure, and is composed of a scattering electron layer and a capturing electron layer; one structure is that the two surface layers are scattering electron layers, and the middle layer is a capturing electron layer; the other structure is that the two surface layers are capturing electron layers, and the middle layer is a scattering electron layer; the scattering electron layer is composed of a composite of polyetherimide and 4-N,N-dimethylaminophenylboronic acid; the capturing electron layer is composed of a composite of polyetherimide and tetrafluorotetracyanoquinoline dimethane.

2. A multilayer polyetherimide energy storage composite dielectric film according to claim 1, characterized in that The volume ratio of 4-N,N-dimethylaminophenylboronic acid to polyetherimide in the scattering electron layer is 0.008:1; the volume ratio of tetrafluorotetracyanoquinoline dimethane to polyetherimide in the capturing electron layer is 0.006:

1.

3. The multilayer polyetherimide energy storage composite dielectric film according to claim 1, characterized in that The thickness of the multi-layered polyetherimide energy storage composite dielectric film is 5 μm to 13 μm; the ratio of the thickness of a single surface layer to the total thickness of the multi-layered polyetherimide energy storage composite dielectric film is (3 to 5):

13.

4. The multilayer polyetherimide energy storage composite dielectric film according to claim 1, characterized in that The two surface layers of the multilayer structured polyetherimide energy storage composite dielectric film are scattering electron layers, and the middle layer is a capturing electron layer. The preparation method thereof is specifically completed according to the following steps:

1. dissolving polyetherimide and 4-N,N-dimethylaminophenylboronic acid in N-methylpyrrolidone, and then performing vacuum defoaming treatment to obtain a bubble-free 4-NB / PEI mixed solution; 2. Dissolving polyetherimide and tetrafluorotetracyanoquinoline dimethane in N-methylpyrrolidone, and then performing vacuum defoaming treatment to obtain a bubble-free F4TCNQ / PEI mixed solution; 3. Scrape the bubble-free 4-NB / PEI mixed solution on the substrate and dry it to form a lower surface composite film, which is the scattering electron layer; Fourth, the bubble-free F4TCNQ / PEI mixed solution is scraped on the lower surface composite film, and then dried to form an intermediate composite film, which is the electron capture layer; 5. The bubble-free 4-NB / PEI mixed solution is scraped on the middle layer composite film, and then dried to form an upper surface composite film, which is the scattering electron layer; a three-layer composite dielectric film is constructed, which is a multi-layer structure polyetherimide energy storage composite dielectric film.

5. The multilayer polyetherimide energy storage composite dielectric film according to claim 1, characterized in that The two surface layers of the multilayer structured polyetherimide energy storage composite dielectric film are electron capture layers, and the middle layer is an electron scattering layer. The preparation method thereof is specifically completed according to the following steps:

1. dissolving polyetherimide and 4-N,N-dimethylaminophenylboronic acid in N-methylpyrrolidone, and then performing vacuum defoaming treatment to obtain a bubble-free 4-NB / PEI mixed solution; 2. Dissolving polyetherimide and tetrafluorotetracyanoquinoline dimethane in N-methylpyrrolidone, and then performing vacuum defoaming treatment to obtain a bubble-free F4TCNQ / PEI mixed solution; 3. Scrape the bubble-free F4TCNQ / PEI mixed solution on the substrate and dry it to form a lower surface composite film, which is the electron capture layer; Fourth, the bubble-free 4-NB / PEI mixed solution is scraped on the lower surface composite film, and then dried to form an intermediate composite film, which is the scattering electron layer; 5. The bubble-free F4TCNQ / PEI mixed solution is scraped on the middle layer composite film, and then dried to form an upper surface composite film, which is the electron capture layer; a three-layer composite dielectric film is constructed, which is a multi-layer structure polyetherimide energy storage composite dielectric film.

6. A multilayer polyetherimide energy storage composite dielectric film according to claim 4 or 5, characterized in that In step one, the volume ratio of 4-N,N-dimethylaminophenylboronic acid to polyetherimide is 0.008:1; in step one, the volume ratio of the total mass of polyetherimide and 4-N,N-dimethylaminophenylboronic acid to N-methylpyrrolidone is (0.15g-0.18g):1mL; in step two, the volume ratio of tetrafluorotetracyanoquinoline dimethane to polyetherimide is 0.006:1; in step two, the volume ratio of the total mass of polyetherimide and tetrafluorotetracyanoquinoline dimethane to N-methylpyrrolidone is (0.15g-0.18g):1mL.

7. A multilayer polyetherimide energy storage composite dielectric film according to claim 4 or 5, characterized in that The vacuum defoaming treatment method described in step 1 and step 2 is: using gradient vacuum treatment, first standing in a vacuum environment of 500mbar and 30°C for 5min to 15min, then standing in a vacuum environment of 100mbar and 30°C for 5min to 15min, and finally standing in a vacuum environment of 10mbar and 30°C for 5min to 15min.

8. A multilayer polyetherimide energy storage composite dielectric film according to claim 4 or 5, characterized in that The drying method described in step 3, step 4 and step 5 is: ①. In an environment with a relative humidity of 40%, keep warm at 70℃ for 4 hours, and then keep warm at 120℃ for 2 hours; ② In an environment with a relative humidity of 30%, keep warm at 150℃ for 2 hours, and then keep warm at 200℃ for 2 hours; ③. In an environment with a relative humidity of 20%, keep warm for 4 hours at 200℃ in a nitrogen atmosphere; ④. Place the film in a nitrogen atmosphere and cool it to room temperature, and control the nitrogen flow along the coating direction.

9. The use of a multilayer polyetherimide energy storage composite dielectric film as claimed in claim 1, characterized in that A multilayered polyetherimide energy storage composite dielectric film is used as a dielectric material of a dielectric capacitor; the dielectric capacitor is used for a high-voltage flexible direct current transmission converter valve, a new energy power generation filter or a new energy vehicle electric vehicle inverter.

10. The use of a multilayer polyetherimide energy storage composite dielectric film as claimed in claim 1, characterized in that A multilayer polyetherimide energy storage composite dielectric film is used in high temperature and high field conditions for electrical energy storage devices. It can achieve a discharge energy density of 6.14 J / cm at a charge and discharge efficiency of 93.26% at 150°C and 620 kV / mm. 3 .

Citation Information

Patent Citations

  • PEI cast film with high energy storage density and high smoothness and preparation method thereof

    CN116262855A

  • Polyetherimide-based energy storage composite dielectric film and preparation method and application thereof

    CN117683350A

  • Lithium acetate / polyetherimide high-temperature energy storage composite dielectric and preparation method and application thereof

    CN118406374A